FUNGSI MEDIA CENTER SEBAGAI MEDIA DISEMINASI INFORMASI PEMERINTAH DAERAH KOTA BENGKULU - ANIS ENDANG SM; SRI NARTI (UNIVED PRESS, Universitas Dehasen Bengkulu, 2021)
Transparency is one of the important principles that must be implemented by government administrators. The principle of transparency can be realized through the dissemination of information to the public, as carried out by the Media Center of the Department of Communication, Information, and State Encryption, Bengkulu City Government. This study aims to explain the function Media Center through the website https://mediacenter.benngkulukota.go.id in disseminating information to the public based on Law No. 14 of 2008. This study uses a qualitative descriptive approach, by interviewing three informants. The results show that the media center has carried out the information dissemination function well, which can be seen from the quality of news writing that meets the rules of journalistic writing and updates news every day.This function can be realized properly because of the competent human resources involved in the team and the support of supporting infrastructure in the process of reporting information, documentation, and managing information and documentation.